The Implementation of Critical Gas Rate in Liquid Loading Well and Optimization Analysis using the Adequacy Chart - Andru Ferdian; Silvya Dewi Rahmawati (Universitas Islam Riau (UIR) Press, 2021)
In the gas well, liquid loading occurs when the gas rate is insufficient to lift liquids into the surface such as water and/or condensate. This causes an accumulation of the liquid in the wellbore, supplies additional backpressure to the formation, and may completely kill the well. Meanwhile, the limited space and typically high cost of offshore operations have made a proper study for optimization selection very essential. The selected project must fulfill several requirements, namely: 1) Fit for the purpose, 2) Low risk and uncertainties, and 3) Economic. Hence, this study will describe the pilot project and continuous improvement process of lowering the gas well pressure using a wellhead compressor and a temporary separator to optimize the liquid loading. It also explains the implementation of critical gas rate in predicting the liquid loading event from the well’s production history. A new analysis method utilizing the adequacy chart was proposed to verify the suitability of the available pressure-lowering system unit available in the market with the well candidates. An adequacy chart was constructed from the well’s deliverability, critical gas rate, and lowering pressure unit or system capacity. These three charts will combine to generate an overlapping area, which signifies suitability for the recommended operation. The well’s production data history can be used to predict the liquid loaded-up event due to the continued decline of the generated gas. Also, a combination of the critical gas rate and decline analyses can predict potential liquid loading problems.